English Teachers’ Digital Competences in a Post-COVID Classroom: A Case Study - Wysocka-Narewska, Marzena (International Journal of Research in E-learning, 2024)
The article addresses the issue of digital competences observed among English teachers in the context of the post-Covid classroom covered by the time frame from September 2022 to 2023. In order to check the level of teachers’ professional digital competences, also known as TPDC, who, according to the current state of research showed a complete lack of such skills in the first period of the pandemic, the retrospective interview was conducted. Next, in September 2022, when the first school year without any Covid-19 restriction began, the teachers underwent a detailed analysis of their competences via a questionnaire based on the European Framework for the Digital Competence of Educators (DigCompEdu), allowing them to self-mark (un)used digital skills during language lessons. Additionally, the teachers’ state of knowledge and skills from this period was compared with their competences at a later stage, in September 2023, to check the impact of such factors as time, previous experience in using the skills and trainings completed on teachers’ functioning in the classroom. The study was composed of four teachers representing two primary schools in Poland. It turned out that the respondents’ knowledge and use of modern technologies was negligible in the first period of the pandemic, as assumed, while their digital competences acquired later on were a matter of time and result of the courses attended. As the study participants reflected different levels of skills, distributed unevenly over time, three different trends in teachers’ (non)development of the above-mentioned competences were outlined. In addition, the profiles of teachers participating in the study were constructed in line with the lists of determinants of teachers’ digital proficiency proposed by the European Framework for the Digital Competence of Educators (DigCompEdu). Following the research findings, it is not teachers’ age, seniority or degree of professional promotion at school that influences their digital skills, but rather their basic knowledge, education and additional functions performed in an institution that immediately impacts the level of modern technology competences. It is recommended to expand the research to measure the competences in question on a larger research sample, as well as look at the very classroom situation from the point of view of real skills (un)used by teachers during language instructions